The Heart in the Mind: A Systematic Review and Meta-Analysis of the Association Between Theory of Mind and Cardiac Vagal Tone - Zammuto, Marta; Ottaviani, Cristina; Laghi, Fiorenzo; Lonigro, Antonia (Frontiers in Physiology, 2021)
Theory of mind (ToM) is the human ability to infer others’ mental states in order to understand their behaviors and plan own actions. In the past decades, accumulating evidence has shown that heart rate variability (HRV), an index of parasympathetic control of the heart, is linked to behavioral regulation, social competence, and social cognition abilities, all implicated -to some extent- in ToM. The present study aimed at systematically reviewing and meta-analyzing the available studies investigating the relation between ToM and HRV in typically developing people. Six studies were eligible for the meta-analysis, yielding a significant association between HRV and ToM of small-to-medium effect size (g = .44). This result was not influenced by publication bias. Due to the low number of studies eligible for the meta-analysis, it was not possible to test the effect of categorial moderators. The moderating role of sex and quality of the studies was examined by meta-regression analysis. Moderation analysis did not yield any significant effect; however, at a descriptive level, studies yielding the largest effect size were characterized by the use of high frequency-HRV assessment at rest and the Reading the Mind in the Eyes Test to evaluate ToM abilities. Results preliminarily suggest that tonic HRV might be used as an indicator of the ability to understand the content of others’ mind.